PENGELOLAAN PENGETAHUAN DI INDUSTRI JASA: STUDI KASUS KONSULTAN PAJAK DAN PERENCANA PERNIKAHAN - Agus Gunawan; Yoke Pribadi Kornarius; Angela Caroline; Adrianus Tirta (Value : Jurnal Manajemen dan Akuntansi, 2023)
Service industries, such as tax consultants and wedding planners, frequently utilize part-time workers to minimize operational costs. However, employing part-time staff can present certain drawbacks, such as the risk of knowledge loss due to high turnover rates. This research aims to explore the disparities in knowledge management practices between two service-oriented companies that employ different strategies for managing part-time employees. The study involved 22 tax consultant employees and 30 wedding planner employees, who participated by completing a questionnaire. Regression analysis was employed to test the relationships among the variables under investigation. The findings of the study reveal that knowledge management significantly influences employee innovative work behavior. Furthermore, variations in knowledge management practices were observed between the two businesses, primarily attributed to their distinct characteristics. This study highlights the importance of recognizing the divergent nature of sectors within the same industry and tailoring policies accordingly to suit their specific needs.